PENGARUH KOMPETENSI DAN TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT PADA BPK RI PERWAKILAN PROVINSI SUMATERA UTARA - Sari, Eka Nurmala; Lestari, Sapta (Program Studi Akuntansi FPEB UPI, 2018)
This study aims to test and analyze whether the competence and time budget pressure affect audit quality. This research was conducted at BPK RI Representative of North Sumatera Province. Data collection techniques in this study are questionnaires and documentation studies. The sample selection was done by Simple Random Sampling method. The population in this study is all auditors working on the environment BPK RI Representatives of North Sumatra Province consisting of 99 auditors. Based on the sampling technique yielded a sample of 50 auditors. Method of data analysis using path analysis.. The results show that the variable of competence and time budget pressure partially and simultaneously have an effect on to audit quality. R square value of 22.55% indicating that the competence and time budget pressure able to explain the audit quality of 22.5% and the remaining 77.5% explained by other variations outside the model.